2007
DOI: 10.1037/0022-006x.75.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Event-level covariation of alcohol intoxication and behavioral risks during the first year of college.

Abstract: The authors examined the global- and event-level associations between alcohol intoxication and 10 behavioral risks during the 1st year of college. Participants (n = 1113; 62% female; 54% Caucasian) completed 30 days of Web-based self-monitoring that assessed alcohol consumption and involvement in 10 behavioral risks. Generalized estimating equations analyses were used to determine which behaviors covaried with event-level versus global indices of intoxication as well as the moderating effects of gender on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(186 citation statements)
references
References 39 publications
(42 reference statements)
12
169
3
2
Order By: Relevance
“…Specifi cally, eventlevel studies make it possible to examine the within-person effects of intoxication-the deviation on a drinking occasion from the individual's own average level of intoxication-on the likelihood of dating violence perpetration. Although the within-person effect of alcohol intoxication on the perpetration of dating violence has not been previously examined, increases in an individual's level of intoxication above their average have been associated with a general measure of aggression (Neal & Fromme, 2007;Quinn et al, 2013). In addition, Quinn and colleagues found that sex moderated this association such that men had a stronger association between increased levels of intoxication and an increased probability of aggression relative to women.…”
Section: Alcohol and Dating Violencementioning
confidence: 86%
“…Specifi cally, eventlevel studies make it possible to examine the within-person effects of intoxication-the deviation on a drinking occasion from the individual's own average level of intoxication-on the likelihood of dating violence perpetration. Although the within-person effect of alcohol intoxication on the perpetration of dating violence has not been previously examined, increases in an individual's level of intoxication above their average have been associated with a general measure of aggression (Neal & Fromme, 2007;Quinn et al, 2013). In addition, Quinn and colleagues found that sex moderated this association such that men had a stronger association between increased levels of intoxication and an increased probability of aggression relative to women.…”
Section: Alcohol and Dating Violencementioning
confidence: 86%
“…Moreover, gender differences show that college men emphasize peer pressure and the risk of embarrassment if they refrain from drinking, whereas college women are more concerned with the negative consequences associated with heavy alcohol use (Suls & Green, 2003). Students exposed to environments where alcohol is widely consumed and where increased salience of positive expectations of alcohol outcomes exists (LaBrie, Grant, & Hummer, 2011) are at greater risk for binge drinking (Weitzman, Nelson, & Wechsler, 2003), and heavy drinking is associated with sexual assault (Abbey, 2002;Mouilso et al, 2012;Neal & Fromme, 2007;Testa & Hoffman, 2012).…”
Section: Other Risk Factors For Sexual Assaultmentioning
confidence: 99%
“…Risk factors for sexual assault include heavy alcohol use (Abbey, 2002;Mouilso, Fischer, & Calhoun, 2012;Neal & Fromme, 2007;Testa & Hoffman, 2012), as well as a history of childhood victimization (Aosved et al, 2011;Smith, White, & Holland, 2003). Positive alcohol expectancies (Marx, Nichols-Anderson, Messman-Moore, Miranda, & Porter, 2000), perceptions of peers' drinking behavior (Small & Kerns, 1993;Young, Morales, McCabe, Boyd, & d'Arcy, 2005), hooking up (Flack et al, 2007;Paul, McManus, & Hayes, 2000), and place of residence (e.g., Greek housing; Minow & Einolf, 2009) have also been found to be risk factors for sexual assault.…”
mentioning
confidence: 99%
“…After making these restrictions, our main sample consists of 29,737 students, or 267,322 student-class observations across 9 fall quarters. 9 We combine these data with readily available reports of the football team's win-loss records, which we use to form our term-specific measures of athletic 7 Other documented behaviors associated with collegiate football include increased crime (Rees and Schnepel 2009) and heavy alcohol consumption (Neal and Fromme 2007;Glassman et al 2007;Glassman et. al.…”
Section: Data Used In Main Analysismentioning
confidence: 99%